Structural–Interpretive Modeling of Audit Firm Ranking in Iran - Saber, Alireza; Alinezhad Sarouklayi, Mehdi; Badavar Nahandi, Younes; Zeynali, Mehdi (Management Strategies and Engineering Sciences, 2027)
The present study was conducted with the aim of developing a structural–interpretive model for ranking audit firms in Iran. The participants were 10 certified public accountants employed in audit firms at the senior supervisor level and above, selected through purposive sampling. Data were collected through semi-structured interviews in the field phase. The interviews continued until theoretical saturation was achieved during the Delphi analysis process. Data were analyzed using the Delphi method and Interpretive Structural Modeling (ISM). The software utilized for the analysis included EXCEL and MICMAC. Based on the Delphi results, the identified components were confirmed. In line with the research objective of identifying the structural–interpretive model for ranking audit firms in Iran, 11 components were validated through the Delphi technique. These components included audit service quality, staff competence and experience, service diversity and complexity, internal quality control, independence and corporate governance, compliance with standards and legal requirements, risk history, violations and litigation records, operational scale and capacity, technology, digitalization and innovation, professional reputation and credibility, and customer satisfaction and loyalty. The resulting interpretive structural model, developed through logical level classification and grounded in expert experience, provides a robust operational framework for audit firms in Iran. Understanding this hierarchy of influence and dependence enables audit firm managers to strategically prioritize their resources. By transforming and strengthening these foundational factors, positive effects can be expected to cascade through higher levels of the hierarchy, ultimately leading to a substantial increase in customer satisfaction and loyalty as the most important indicator of overall organizational success.